Model Cabut-Serat Nylon 600 Tertanam Dalam Matriks Sementitis Berbasis Fraktur - Retno Susilorini (Universitas Muhammadiyah Yogyakarta, 2008)
The fracture mechanics is known as a fracture based approach to prohibit a catastrophic failure of structure. In micro scale field, the fracture mechanics is implemented especially to determine the performance of interface between fiber and cementitious matrix in ‘fiber-reinforced cementitious composite’. The studies and applications of nylon clearly define the advance characteristic of nylon may influence the overall performance of composites and become a crucial issue to be learned, therefore, this paper forwards a fractured based pull-out model of short nylon 600 embedded in cementitious matrix with main concern on fracture phenomenon. The research applies experiment that applies pull-out test with embedded nylon 600 in cementitious matrixand the analytical method that constructs the fractured based pull-out model. The experiment results show the specimens with pull-out fibers have embedded length lf = 30-60 mm and the broken fibers lf = 70-100 mm. The pull-out test also shows several stages: (a) Pre-slip stage, (b) Slip stage, and (c) Strain-hardening stage. The model fits to experimental results. Several theories meet conclusions: (a) Whenever fracture takes place, it is always an unstable crack, (b) Stable cracks are established by the presence of crack arrester, (c) There is no way directly to determine the length of stable crack, but it still can be determined by fractured based approach, (d) The length of stable crack is determined by the position of crack arrester, (e) There is an equation derived for pull-out model (f) There is an equation to determine the stable crack length, (g) Stable cracks may be used to determined the bond capacity, (h) After the establishment of stable cracks, increasing strain beyond strain e1 will not increase stress s1, hence do not induce additional fracture, (i) Increasing of strain e after the establishment of stable cracks will increase stress s, then the second slip will not take place, (j) Broken nylon fibers have a longer embedded length because of the possibility of crack arrester presence is bigger than the shorter ones.